2000
DOI: 10.1002/1097-0215(20001001)88:1<82::aid-ijc13>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

p53 mutational spectra are different between squamous-cell carcinomas of the lip and the oral cavity

Abstract: We studied the p53 mutational spectra of 34 lip and 60 intra‐oral squamous‐cell carcinomas and examined possible etiological and prognostic correlations for these tumor sites. For the p53 analysis of exons 5–8, we used PCR/TGGE screening followed by DNA sequencing. Mutations were found in 18/34 (53%) lip and 22/60 (38%) intra‐oral carcinomas. The p53 mutational spectrum of the intra‐oral carcinomas comprised transitions and transversions in nearly equal frequency (11 to 10). In comparison, transitions were 3.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1
9

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 21 publications
5
29
1
9
Order By: Relevance
“…12,29 -31 The p53 mutation spectrum differs between squamous cell carcinoma of the lip and the oral cavity, indicating divergent exposure to carcinogenic agents. 32 We examined primary and recurrent squamous cell carcinomas from different locations of the head and neck and failed to observe site-specific mutation patterns when stratifying according to tumour location. Our mutation patterns of G:C3 T:A transversions in both primary and recurrent squamous cell carcinomas may indicate a carcinogenic effect of tobacco smoke in our patients.…”
Section: P73mentioning
confidence: 99%
“…12,29 -31 The p53 mutation spectrum differs between squamous cell carcinoma of the lip and the oral cavity, indicating divergent exposure to carcinogenic agents. 32 We examined primary and recurrent squamous cell carcinomas from different locations of the head and neck and failed to observe site-specific mutation patterns when stratifying according to tumour location. Our mutation patterns of G:C3 T:A transversions in both primary and recurrent squamous cell carcinomas may indicate a carcinogenic effect of tobacco smoke in our patients.…”
Section: P73mentioning
confidence: 99%
“…22 Estudos epidemiológicos verificam uma elevada frequência de indivíduos com lesões labiais submetidos a tal fator, 3,4,23 sendo este maior contato com os raios solares em virtude de atividades ocupacionais ao ar livre. 8,23 O elevado índice de radiação ultravioleta no Rio Grande do Norte 12 remete a uma maior preocupação para conhecer o perfil epidemiológico de enfermidades relacionadas a tal fator etiológico.…”
Section: Resultados Resultados Resultados Resultados Resultadosunclassified
“…A study of 94 oral squamous cell carcinomas (OSSC) found that 43% had TP53 mutations (Ostwald, 2000), similarly another study observed 48.66% of OSSC had p53 mutations (Hsieh, Wang et al 2001). An analysis of 18 oral tumours found 72% had TP53 mutation, however this high incidence may have been due to the small sample size (Partridge, 2000).…”
Section: Mrnasmentioning
confidence: 97%
“…One investigation observed the highest number of mutations occurred in exon 7 and that the type of SNP was characteristic of lesion location. Lip lesions exhibited G:C to A:T transitions while intra-oral lesions exhibited an equal frequency of transitions and transversions (G:C to T:A) (Ostwald C, Gogacz P et al 2000). It has been proposed that these transversions are preferentially induced by breakdown products of benz[a]pyrenes, suggesting a strong correlation with tobacco usage (Ostwald C, Gogacz P et al 2000).…”
Section: Mrnasmentioning
confidence: 99%
See 1 more Smart Citation